Batik T-Shirt Design for Generation Z - Maitri Widya Mutiara; Viola Brigitta Japri; Jennifer Evelyn Gunawan; Agness Yesica; Dominique Jesslyne Suwito (Gorga : Jurnal Seni Rupa, 2025)
Batik is one of Indonesia’s cultural heritages that holds significant historical, philosophical, and aesthetic value. As a symbol of national identity, its preservation requires innovative approaches to remain relevant in the face of changing times. In the current context, Generation Z—who are in their productive years and exert substantial influence on fashion trends and consumer behavior—show a declining interest in traditional Batik due to perceptions of impracticality and incompatibility with modern lifestyles. This study aims to design Batik-patterned T-shirts that align with the visual preferences of Generation Z, with the objective of increasing appreciation and pride in local culture through casual fashion media. A quantitative research method was employed, utilizing an online survey distributed to Generation Z respondents. The questionnaire gathered data on favored motifs, aesthetic preferences, and perceptions of Batik in contemporary fashion contexts. The collected data were analyzed statistically and presented in the form of diagrams. The findings indicate a strong interest in Batik motifs when integrated into modern and minimalist T-shirt designs. This study is expected to contribute to the development of culture-based fashion products and serve as a strategic approach to preserving Batik in a manner that is inclusive and adaptable to the tastes of today’s younger generation.